Investigating Students’ Perceptions of Artificial Intelligence in Medical Education: A Cross-Sectional Study - Saba Iqbal; Humaira Shamim; Muhammad Moosa; Farrukh Hayat Khan; Saba Farooq; Arifa Zafar (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Artificial Intelligence (AI), recognized as the fourth industrial revolution, is revolutionizing medical practice through enhanced diagnostics, treatment planning, and healthcare delivery. Its expanded role post-COVID-19 underscores the urgency of AI literacy among future physicians. This study aimed to explore medical students’ perceptions of AI in medical education.